Other Games, Other Histories - Byrd, Jodi A. (ROMchip, 2019)
What could a history of game studies be from the perspective of a queer Chickasaw feminist scholar? Should this be a disciplining manifesto, a polemical call to arms for radical transformation, a survey of the existing scholarship that has thus far framed games ludologically as fun, as sportsmanship, as design, or as epic struggles for political power where the player rather ominously wins or dies? I’m a bit of an interloper as a recent arrival from Indigenous studies to video-game studies, a field that represents both the end of history and the ahistoricity of pop-culturally–oriented archives that are presentist at best, and at worst, complicit with an industry derived from settler militaristic technologies and platforms and compelled by niche markets to innovate faster and faster to saturate more and more households at the structural level of occupation. And then there is the problem of what the history of game studies has been: Greco-Roman, European, cis white male, heterosexual, orientalist, algorithmic, and code driven with the techno-optimism of Silicon Valley alongside Jane McGonigal’s fundamental belief that games have and will save the world once they unite the collective brain power of all the gamers and bend them to a single task—and if not all that, then peak 1980s geekery with a hint of liberal multiculturalism thrown in, if Ernest Cline’s Ready Player One is anything to go by. It is as if the history of game studies has only ever been an imperial read-only memory to be mined, played, and spatialized within the conscriptions of conquistador archives already known and yet to be discovered.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Afterlives of Indigenous archives: essays in honor of The Occom Circle - Schweitzer, Ivy; Henry, Gordon (Dartmouth College Press, 2019)
"Afterlives of Indigenous Archives offers a compelling critique of Western archives and their use in the development of “digital humanities.” The essays collected here present the work of an international and interdisciplinary group of indigenous scholars; researchers in the field of indigenous studies and early American studies; and librarians, curators, activists, and storytellers. The contributors examine various digital projects and outline their relevance to the lives and interests of tribal people and communities, along with the transformative power that access to online materials affords. The authors aim to empower native people to re-envision the Western archive as a site of community-based practices for cultural preservation, one that can offer indigenous perspectives and new technological applications for the imaginative reconstruction of the tribal past, the repatriation of the tribal memories, and a powerful vision for an indigenous future."
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Learning, Education & Games, Volume 3: 100 Games to Use in the Classroom & Beyond - Schrier, Karen (ETC Press, 2019)
Have you ever wanted to know which games to use in your classroom, library, or afterschool program, or even at home? Which games can help teach preschoolers, K-12, college students, or adults? What can you use for science, literature, or critical thinking skills? This book explores 100 different games and how educators have used the games to teach - what worked and didn't work and their tips and techniques. The list of 100 goes from A to Z Safari to Zoombinis, and includes popular games like Fortnite, Call of Duty: Modern Warfare, and Minecraft, as well as PC, mobile, VR, AR, card and board games.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé